Analisis Lembar Kerja Peserta Didik (LKPD) Matematika Kelas X - Rayanti, Novi; Nidya Nina Ichiana; Rezkianti Hasan (Alauddin Journal of Mathematics Education, 2022)
This study aims to determine the quality of the Mathematics Student Worksheets (LKPD) of Class X Semester I used at SMA Negeri 19 Bulukumba. The quality of the mathematical LKPD analyzed in terms of didactic requirements, construction requirements, and technical requirements. This research is a descriptive research with a quantitative approach. The data in this study were analyzed descriptively-quantitatively. The results of this study indicate that the quality of the mathematics worksheets for class X Semester I at SMA Negeri 19 Bulukumba is in the good category as teaching materials used in the school. The details of the quality of the mathematics LKPD class X Semester I at SMA Negeri 19 Bulukumba, namely; (1) The quality of the mathematics LKPD class X semester I at SMA Negeri 19 Bulukumba in terms of the didactic requirements obtained an ideal percentage of 74.06% in the good category, (2) The quality LKPD mathematics class X semester I SMA Negeri 19 Bulukumba in terms of construction requirements obtained the ideal percentage is 76.08% with good category. Meanwhile, the quality of the first semester of class X mathematics LKPD at SMA Negeri 19 Bulukumba in terms of technical requirements obtained a percentage of 72.95% with a fairly good category.